2023
DOI: 10.3390/rs15040873
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Downscaling of GRACE Data Based on XGBoost Model for Improved Understanding of Hydrological Droughts in the Indus Basin Irrigation System (IBIS)

Abstract: Climate change may cause severe hydrological droughts, leading to water shortages which will require to be assessed using high-resolution data. Gravity Recovery and Climate Experiment (GRACE) satellite Terrestrial Water Storage (TWSA) estimates offer a promising solution to monitor hydrological drought, but its coarse resolution (1°) limits its applications to small regions of the Indus Basin Irrigation System (IBIS). Here we employed machine learning models such as Extreme Gradient Boosting (XGBoost) and Arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 124 publications
0
14
0
Order By: Relevance
“…Laser-induced breakdown spectroscopy provides high spatial resolution and real-time measurement, but it may have lower sensitivity for low concentrations and be affected by soil properties. The choice of remote sensing technique depends on the specific application and the trade-off between accuracy, speed, cost, and complexity [ [44] , [45] , [46] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-induced breakdown spectroscopy provides high spatial resolution and real-time measurement, but it may have lower sensitivity for low concentrations and be affected by soil properties. The choice of remote sensing technique depends on the specific application and the trade-off between accuracy, speed, cost, and complexity [ [44] , [45] , [46] ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mirzaei et al [ 9 ] confirmed that the recycling received from Sentinel-2 satellite images has an inverse relationship with the concentration of heavy metals. It can be justified that the presence of heavy metals leads to the inactivation of waves in the visible and infrared parts, resulting in the inverse relationship between reflection and detectable amounts of heavy metal concentration [ [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. Factors such as iron oxides or clays and high levels of organic matter, which have been identified as influencing factors on the number of heavy metals, play a role in the inverse relationship between reflection and detectable amounts of heavy metal concentration [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Downscaling is a common issue in the subject of satellite remote sensing [9]. Normally, the downscaling methods include dynamic and statistical downscaling [3,5,14]. Dynamic downscaling is used to construct a regional numerical model at higher spatial resolution; thus, it can be applied in local areas at smaller scales.…”
Section: Downscaling Methodsmentioning
confidence: 99%
“…It includes a bay, which is up to 240 m wide, separating the Western bay called “Paddi Zirr,” which is up to 9.1 m deep, and the Eastern bay called Demi Zirr, which is the deep-water bay, providing the land to Gwadar port [ 45 ]. The Gwadar foreland consists of two of the highest peaks, known as Koh-i-Batel, which is up to 137 m high, spreading up to 11 km, and Koh-i-Mehdi, 340 m tall [ 3 , 10 , 40 , 42 , 46 ].…”
Section: Methodsmentioning
confidence: 99%